An Ethiopic 'Homily on Peter' attributed to Ephrem - Aaron Michael Butts; Ted Erho; Jonas Karlsson (Aethiopica)
An edition, with English translation, is provided of an Ethiopic ‘Homily on Peter’, attributed to Ephrem the Syrian (d.373), which is uniquely attested in MS Ethio-SPaRe UM-046, fols 148v–151v. This Ethiopic homily ultimately goes back—undoubtedly via Arabic—to a Syriac stanzaic poem (soḡiṯā) recently edited by S. P. Brock.